Structural geometry and gold ores along the first outlined N–S dextral shear zone in the Egyptian Nubian Shield, East African orogenic belt: New insights from integrated remote sensing, gravity, magnetic and field studies - Mohamed A. Abd El‑Wahed; Samir Kamh; Mohamed Attia; Ahmed M. Eldosouky (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract This study outlines the newly identified N–S dextral shear zone within the Egyptian Nubian Shield. The N–S Shear Zone (600–590 Ma) is a significant north-trending geological feature in the Egyptian Nubian Shield, extending over 140 km in length and reaching widths of up to 10 km. The N–S shear zone area is composed mainly of mylonitic schist, metavolcanics, metasediments, augen gneisses, and molasse sediments. The combination of remote sensing, magnetic analysis, and fieldwork in structural mapping has been extensively used, with developments in remote sensing technologies facilitating comprehensive structural geology mapping. Two Landsat-8 OLI/TIRS scenes with 30 m spatial resolution were used to upgrade the geologic map and extract major geological structures in a study area. Image kinematic indicators of the N–S shear zone (N–SSZ) were enhanced using processed remote sensing data. Geophysical magnetic and gravity data were used to unravel shallow and deep structures, with geophysical data analysis and edge detection interpretation revealing significant structural directions in the region. The gravity and magnetic data were upward continued to altitudes of 1, 2, and 4 km. Then, the Enhanced Horizontal Gradient Amplitude (EHGA) was applied to RTP and Bouguer and their upward continued data to delineate shallow and deep structures. The Bouguer anomalies outline N–S, NW, and E–W-directed structures, while magnetic data underline a previously unrecognized N–SSZ. The N–SSZ is characterized by a transpressive deformation regime, featuring a sub-horizontal pure shear component operating in conjunction with simple shear. As the deformation gradient intensifies, the influence of the simple shear component escalates, becoming the dominant factor in the ultramylonites located at the core of the shear zone. The N–S shear area is characterized by conjugate shear zones that emerged during the Najd Orogeny. The dominant shear plane is oriented in a NW–SE direction, while additional shear zones trending NE–SW and N–S serve as conjugate structures. Riedel structures create a network of shear bands, with the N–S dextral shear recognized as the X-shear. The N–SSZ plays a crucial role in controlling gold mineralization as well as other ore minerals such as chromite, copper, and nickel.